Advantage of Using of High-Sensitivity Troponin I Compared to Conventional Troponin I in Shortening Time to Rule out/in Acute Coronary Syndrome in Chest Pain Patients Presenting to the Emergency Department - Ziwei Lin; Patrizia Cardelli; Rossella Marino; Swee Han Lim; Salvatore Di Somma (Medicina, 2022)
Background and Objectives: We aimed to compare the time to diagnosis for acute coronary syndromes using high-sensitivity troponin I (hsTnI) and conventional troponin I (TnI) in patients presenting to the emergency department (ED) with chest pain. Materials and Methods: This was an observational prospective study involving patients presenting to the ED of Sant’Andrea Hospital University la Sapienza in Rome (Italy) with chest pain from January to December 2014. Serum troponin was drawn at presentation, and at 3, 6, 9, and/or 12 h if clinically indicated. Depending on date of recruitment, patients had either hsTnI (Abbott Laboratories) or TnI (Abbott Laboratories) performed. The primary endpoint was the time to diagnosis at index visit. Results: A total of 1059 patients were recruited, (673 [63.6%] male, median age 60 years [interquartile range 49–73 years]), out of whom 898 (84.8%) patients were evaluated with hsTnI and 161 (15.2%) with TnI. A total of 393 (37.1%) patients had the diagnosis of acute coronary syndrome in ED. The median time to diagnosis for those evaluated with TnI was 400 min, IQR 120–720 min, while the use of hsTnI led to a significantly shorter time to diagnosis (median 200 min, IQR 100–200 min, p < 0.001). Conclusions: This study confirms that in patients presenting to the emergency department with chest pain, the use of hsTnI is associated with a reduced time to ruling in/out ACS, and, consequently, hsTnI should be routinely used over TnI for more rapid identification of ACS with benefits for patients and related costs.